Translation of the Chinese version of the Self‐Care for Aspiration Pneumonia Prevention Scale and its validation among Chinese community dwelling elderly with risk of dysphasia - Zhen Yang; Fengmin Chen; Yibo Zhang; Sien Pan; Yingying Lu; Huijun Zhang (Wiley, 2022)
Abstract Aim To translate the Self‐Care for Aspiration Pneumonia Prevention Scale into the Chinese and validate its reliability and validity among community dwelling elderly with risk of dysphasia. Design A cross‐sectional survey. Methods A total of 430 elderly with risk of dysphasia were recruited. The reliability was measured by internal consistency, split half reliability, and test-retest reliability. The validity was evaluated by expert consultation and factor analysis. Results The translated scale had ideal reliability. The content validity index (S‐CVI) was 0.952. The 3‐factor structure, supported by the eigenvalues, total variance explained, and scree plot, was obtained by using exploratory factor analysis. And as a result of a confirmatory factor analysis, the model fitting indexes were all in the acceptable range. The Chinese version of the Self‐Care for Aspiration Pneumonia Prevention scale can contribute to clinical practice and education to improve self‐care for aspiration pneumonia prevention among elderly at risk of dysphasia.